EFFECT OF PROSTAGLANDIN F2a AND OXYTOCIN ON SEMINAL CHARACTERISTICS IN CHHOTTANAGPURI RAMS - KUMAR SINGH, AMIT RANJAN; KUMAR JHA, DILIP; SINGH, M P; SINGH, SRINIWAS (The Indian Journal of Animal Reproduction, 2023)
A study was conducted on chhottanagpuri ram to see the effect of oxytocin and prostaglandin F2a onseminal characteristics. Immediately after semen collection, all the semen samples were brought to the laboratoryand were evaluated for colour, ejaculate volume, mass activity, pH, sperm concentration, live sperm percentageand abnormal sperm percentage. There was significant (p
Keywords: Prostaglandin F2 alpha; Oxytocin; Chhottanagpuri ram; Semen